SIFAT FISIK DAN KIMIA WOOD PELLET DARI LIMBAH INDUSTRI PERKAYUAN SEBAGAI SUMBER ENERGI ALTERNATIF - Effendi Arsad (Jurnal Riset Industri Hasil Hutan, 2014)
Carakteristic physical and chemistry of Wood pellet from Industrial Disposal of Wood as Sources  Energy Alternatif The research to gaved for physical and chemistry of Wood pellet from Industrial. Processing approximately 12%, sawdust dried to moisture content of  sieved that is size of 15 mesh, 25 mesh and 35 mesh. Heating temperature were 60 0C and 110 0C. Moisture content of flawer wood pellet 4,46% - 9,95%, acacia wood pellet were 4.38% - 7.52% and tarap wood pellet were  4.60% - 9.98%. Density of flawer  wood pellet  were 0.51 - 0.78, acacia wood pellet were 0.61 - 0.78 and tarap wood pellet were   0.56 - 0.71, ash content of wood  flawer  from 0.87 - 2.04%, acacia 0.54 - 0.94% and ash content of  tarap wood 1.71 - 2.05%. Calorific value of wood pellets flawers wood 3921,12 - 4150,19 cal/g, acacia wood 4022,29 - 4254,91 cal/g and tarap wood  3920,13 - 4125,28 cal/g. The higher temperature of the heating effect on reality the reduction of water and the weight of ash wood pellets  while it was increasing calorific value.Keywords: waste wood, flawers wood, acacia wood, tarap wood, wood pellet